Investigating Students Motivation on Phubbing during EFL Teaching and Learning Session - Ratna Elia; Nuskhan Abid (Lingual: Journal of Language and Culture, 2025)
The phenomenon of phubbing is increasingly found in English as a Foreign Language (EFL) learning, especially when smartphone use distracts students from interactions and the material being presented. This study aims to identify the internal and external motivations that drive students to phubbing during EFL learning. This study used a qualitative phenomenological design with five participants selected through purposive sampling. Data were collected through semi-structured interviews via WhatsApp and analysed using open, axial, and selective coding. The results revealed five main motivations: boredom and monotonous learning, notifications and checking habits, academic use, social influence, and coping strategies for boredom and difficulty understanding the material. These findings confirm that phubbing is not only triggered by technology, but also by psychological, social, and learning conditions. The implications of this study emphasize the importance of varied learning strategies and managing technology use in the classroom.